The Effect of Networking Capacity on Social Capital and Its Implications for Ease of Access to Financial Capital - Widjanarko, Hendro; Utomo, Humam Santosa; Tjahjanti, Rosalia Dwi Fadma; Suratna, Suratna; Muqaddas, Fadli Hasan (RSF Conference Series: Business, Management and Social Sciences, 2025)
This study examines how the networking capabilities of processed food micro-enterprise owners influence the formation of social capital and how this social capital, in turn, influences ease of access to financial capital. The focus of the study was processed food micro-enterprises in Bantul Regency, Yogyakarta. Using a questionnaire distributed to 100 micro-enterprise owners selected through purposive sampling, this study examined the direct relationship between networking and social capital and the mediating relationship between social capital and access to financial capital. Data analysis used SEM-PLS. The results showed that networking significantly influenced business owners' social capital and access to financial capital. This study also found that social capital significantly influenced access to financial capital. These findings reinforce the literature demonstrating the central role of social networks in expanding financing opportunities for small and medium enterprises.